(untitled) (Eurasian Journal of Ecology, 2016)
Keys of determinant of families by water plants Sparganiaceae Rudolph, Zosteraceae Dum., Najadaceae Juss., Juncaginaceae Rich. according to modern taxonomiccal system in the Kazakh language are given in this article. It is made keys definition of genus and types of family Sparganiaceae Rudolph genus Sparganium L. – 4 types: S. stoloniferum Buch.-Ham., S. microcarpum (Neum.) Celak., S. simplex Huds., S. minimum Hill., of family Zosteraceae Dum. genus Zostera L. – 1 type: Z. minor (Cavol.) Nolte., of family Najadaceae Juss. genus Najas L. – 3 types: N. marina L., N. graminea Delibe., N. minor All., of family Juncaginaceae Rich. genus Triglochin L. 2 types: T. maritima L., T. palustris L.